Plasmodium falciparum: inhibition/reversal of cytoadherence of Thai isolates to melanoma cells by local immune sera. - Singh, B; Ho, M; Looareesuwan, S; Mathai, E; Warrell, D; Hommel, M (1988)
The effect of sera on the cytoadherence in vitro of Plasmodium falciparum-infected erythrocytes to melanoma cells was examined. Sera from 19 healthy individuals living in endemic malarious areas in Thailand and 24 patients with P. falciparum malaria were tested against four local P. falciparum isolates. Out of 57 sera examined, 12 (21%) showed significant inhibition (greater than 50%) of cytoadherence for at least one isolate. Anti-malarial IgG antibody titres were determined for all 57 sera and although 11 of the 12 inhibitory sera had relatively high titres, 36 out of 47 sera with similarly high titres showed no significant inhibitory activity. Convalescent sera were no more effective than corresponding acute sera in inhibiting the cytoadherence of erythrocytes infected with any of the four heterologous isolates examined. Sera which significantly inhibited cytoadherence were also capable of reversing cytoadherence, and pooled plasma, from healthy individuals living in malarious areas, was effective in significantly reversing the in vitro cytoadherence of all the five parasite isolates examined. The results confirm the antibody mediated strain-specific nature of the inhibition of cytoadherence and stress the difficulty in selecting immune sera potentially useful for the immunotherapy of cerebral malaria patients in Thailand.